С. А. Гратинич. Массово-политическая работа Компартии Молдавии (1944—1950) - Зінченко, Ю. І. (Український історичний журнал, 2025)
С. А. Гратинич. Массово-политическая работа Компартии Молдавии (1944—1950). Кишинев : «Штиинца», 1989. — 152 с.